ANGI-07. NOVEL FUSION GENE PTPRZ1-MET PROMOTES GLIOMAS ANGIOGENESIS BY UP-REGULATING EXOCRINE PROTEIN IGF2BP3. (11th November 2019) - Liu, Yanwei; Qiu, Xiaoguang; Jiang, Tao
Abstract: We previously reported a novel fusion gene PTPRZ1-MET in 15% of secondary GBM (sGBM). Subsequent studies showed that ZM fusion indicates a significantly worse prognosis and promotes glioma progression by increasing MET activity. We have demonstrated hyper-activation of MAPK and STAT3 signaling and elevated angiogenesis activities in patients and subcutaneous tumors with ZM fusion. However, the angiogenesis mechanism regulated by ZM is still unclear. In this study, 66 up-regulated and 66 down-regulated genes were identified on 8 sGBMs with ZM fusion comparing gene expression with 135 negative sGBMs (fold-change >2.5 & p.value < 0.05). ZM-harboring U87 MG xenograft models were conducted and RNA sequencing was performed in 3 subcutaneous tumors with ZM-harboring U87 MG and 3 negative control. 384 up-regulated and 698 down-regulated genes were identified on 3 ZM-harboring samples comparing gene expression with 3 negative control samples (fold-change >2.5 & p.value < 0.05. Three subcutaneous tumors with ZM-harboring U87 MG were treated by a MET kinase inhibitor, PLB-1001. Finally, the expression of 13 up-regulated gene decreased and 10 down-regulated genes increased after treatment by PLB-1001. We overlapped the candidate genes between patient samples and subcutaneous tumors and 5 up-regulated and 4 down-regulated genes was appeared and most associated with ZM fusion. Prognostic analysis of 9 candidate genes on sGBM revealed that a higher expression of IGF2BP3 indicates a worse prognosis. In further study, we found that IGF2BP3 can be secreted out of the gliomas stem cells (GSCs) and promote proliferation of vascular endothelial cells and the expression of CD31. IGF2BP3 siRNA can block this pathway and inhibit the angiogenesis. Conclusion, our study demonstrated a new pathway promoting angiogenesis in gliomas. But the regulating mechanism between ZM fusion gene and IGF2BP3 deserves to do further research.